A Comprehensive Literature Review on the Role of Religion in Public Policy - Septiadi, Muhammad Andi (Religion and Policy Journal, 2023)
Research Problem: This comprehensive literature review addresses the intricate and multifaceted relationship between religion and public policy. It seeks to understand how religious beliefs, institutions, and actors influence the formulation and implementation of public policies across different societies and historical contexts. Research Purposes: The primary purpose of this review is to critically analyze existing scholarly works to elucidate the complex interplay between religion, politics, and policy-making. It aims to examine the evolving dynamics of this relationship, explore key theoretical frameworks, and assess empirical findings to offer insights into the role of religion in shaping public policies. Research Methods: Methodologically, this review draws from an extensive body of literature, including scholarly articles, books, and reports. It employs a critical analysis approach to synthesize existing research on the influence of religious beliefs, institutions, and actors on public policy formulation and implementation. Results and Discussion: The review synthesizes existing research to provide insights into the enduring debates, controversies, and nuances surrounding the role of religion in shaping public policies. It discusses key theoretical frameworks and assesses empirical findings to elucidate the complex dynamics of the relationship between religion and public policy across various societies and historical contexts. Research Implications and Contributions: This literature review contributes to a deeper understanding of the pivotal intersection between religion and public policy in the modern world. By critically analyzing existing research, it offers insights into the influence of religious beliefs, institutions, and actors on policy-making processes. Additionally, it highlights the enduring debates and controversies surrounding this relationship, paving the way for further research and discussion in this field.